677.01 ANALYSIS OF RESEARCH ON CHANGING THE SURFACE OF THE GRID IN A DEVICE FOR CLEANING COTTON FROM FINE IMPURITIES - Qozoqov, Saidmuxtor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article analyzes scientific research carried out to improve the design of machines for cleaning cotton from small impurities at cotton ginning enterprises, which have a mesh surface, which is one of the main working parts of the machine for cleaning cotton from small impurities, analyzes were carried out and an optimal mesh surface was proposed.